Is Visual Perceptual Narrowing an Obligatory Developmental Process? - Sorcinelli, Andrea; Vouloumanos, Athena (Frontiers in Psychology, 2018)
Perceptual narrowing, or an increased perceptual sensitivity to frequently encountered stimuli at the expense of sensitivity to infrequently encountered stimuli, has been observed in unimodal speech and visual perception, as well as in multimodal perception, leading to the suggestion that it is a fundamental feature of perceptual development. However, recent findings examining temporal dynamics, rather than standard overall looking time, suggest that perceptual narrowing of multimodal perception might not be obligatory. Across two experiments, we assess perceptual narrowing in unimodal visual perception using remote eye-tracking. We compare adults’ looking at human faces and monkey faces of different species, and present analyses of standard overall looking time and temporal dynamics. As expected, adults discriminated between different human faces, but, unlike previous studies, they also discriminated between different monkey faces. Temporal dynamics revealed that adults were faster to discriminate human than monkey faces, suggesting a processing advantage for conspecifics compared to other animals. Adults’ success in discriminating between faces of two unfamiliar monkey species calls into question whether perceptual narrowing is an obligatory developmental process. Humans undoubtedly diminish in their ability to perceive distinctions between infrequently encountered stimuli as compared to frequently encountered stimuli, however, consistent with recent findings, this narrowing should be conceptualized as a refinement and not as a loss of abilities. Perceptual abilities for infrequently encountered stimuli may be detectable, though weaker compared to adults’ perception of frequently encountered stimuli.